Evaluasi Penempatan Pegawai Pada Badan Kepegawaian Dan Pengembangan Sumber Daya Manusia Kabupaten Merauke - Maria Margareta Reginaldis; Johanis Ohoiledyaan (Madani: Jurnal Politik dan Sosial Kemasyarakatan, 2020)
This study aims to determine (1) employee placement in accordance with the evaluation criteria at the Merauke Regency Personnel and Human Resources Development Agency, (2) the principles of assigning employees to the Merauke Regency Personnel and Human Resources Development Agency, (3) challenges in placement employees at the Merauke Regency Civil Service and Human Resources Development Agency. This research is a qualitative descriptive study. The research informants were the Head of the Personnel and Human Resources Development Agency of Merauke Regency, the Secretary of the Agency, the Head of the Personnel Administration, the Head of the Program and Evaluation Subdivision. The data collection techniques used were observation, interview and documentation. Data analysis uses the steps of data collection, data reduction, data presentation, and drawing conclusions. The results showed that the implementation of the evaluation of the placement of employees according to the evaluation criteria and placement principles was optimal and also not fully optimal, because there were still some obstacles, however, there were strategic steps taken so that the problem could be resolved. There are challenges in implementing employee placement, however these challenges are handled wisely and can be resolved immediately. In principle, the Merauke Regency Personnel and Human Resources Development Agency has taken strategic steps in dealing with existing problems and constraints so that the achievement of organizational goals can be achieved, in accordance with the programs that have been set.